Baseline medical comorbidities in adults randomized in the STRIDE trial for psychostimulant use disorders. Issue 3 (15th March 2016) - dela Cruz, Adriane M.; Carmody, Thomas; Greer, Tracy L.; Rethorst, Chad D.; Warden, Diane; Walker, Robrina; Trivedi, Madhukar H.
Abstract : Background and Objectives: Rates of medical illnesses may be higher among individuals with substance use disorders, complicating their care. This study aimed to expand the understanding of other medical conditions in treatment‐seeking adults with stimulant use disorder (SUD) using data from Stimulant Reduction Intervention using Dose Exercise (STRIDE), a randomized, multisite trial investigating exercise augmentation of treatment as usual. Methods: Utilizing STRIDE baseline data, we examined demographic and clinical characteristics based on the number of self‐reported diagnosed medical conditions among participants meeting eligibility criteria (passing medical screening exam and maximal exercise test, non‐opioid dependent, no concomitant beta blocker, or opioid replacement therapy). Results: The majority (59%) of study participants ( N  = 302, mean age all participants = 39 years) did not report any history of other medical problems. Those with two or more conditions were older (mean age 46 years), reported more pain and worse physical functioning, and more psychiatric disorders (average 1.44). Hypertension was more common among participants with cocaine use disorders only (present in 16%) and liver disease was more common in those with cocaine plus other stimulant use disorders (present in 7%). Conclusion and Scientific Significance: In this sample, patients with SUD were in surprisingly good health. A subpopulation had an overall higher burden of illness with worsened physical and psychiatric functioning. Provision of coordinated care may optimize treatment outcomes for patients based on medical comorbidity burden as well as type of drug abused, although these conclusions should be considered preliminary as they are based on self‐reported data. (Am J Addict 2016;25:215–220)